2021
DOI: 10.3390/biom11030456
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Catestatin Levels and Advanced Glycation End Products in Patients on Hemodialysis

Abstract: Catestatin (CST) is a pleiotropic peptide involved in cardiovascular protection with its antihypertensive and angiogenic effects. Considering that patients with end-stage renal disease (ESRD) who are undergoing hemodialysis (HD) are associated with higher cardiovascular risk, the aim of this study was to investigate plasma CST levels in HD patients, compare them to healthy controls and evaluate possible CST associations with advanced glycation end products (AGEs) and laboratory, anthropometric and clinical par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 73 publications
0
11
0
4
Order By: Relevance
“…Luketin M et al described a negative correlation between AGEs, LDL-cholesterol, triglycerides, and BMI in hemodialysis patients and a positive association between AGEs and malnutrition [ 46 ]. sRAGE was of limited significance, instead, in identifying malnutrition in hemodialysis patients [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Luketin M et al described a negative correlation between AGEs, LDL-cholesterol, triglycerides, and BMI in hemodialysis patients and a positive association between AGEs and malnutrition [ 46 ]. sRAGE was of limited significance, instead, in identifying malnutrition in hemodialysis patients [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…In obese pediatric subjects, our study showed that plasma catestatin levels were significantly lower in obese subjects in comparison to non-obese counterparts (10.57 ± 5.13 vs. 13.49 ± 6.18 ng/mL, p < 0.05). Furthermore, when dividing obese subjects in two groups according to the presence of metabolic syndrome, catestatin was significantly lower in the subgroup of obese children with concomitant metabolic syndrome (8.52 ± 3.89, p < 0.05), showing that the evidence in mice models regarding the role of catestatin in metabolic disorders translated to the clinical setting [ 81 , 82 ].…”
Section: Role Of Catestatin In Various Cardiovascular Disordersmentioning
confidence: 99%
“…[32][33][34][35][36] Although pancreastatin (PST: hCgA 250-301 ) is an anti-insulin and proinflammatory peptide, 37,38 catestatin (CST: CgA 352-372 ) is a proinsulin and anti-inflammatory peptide 39,40 and is a risk factor for cardiovascular diseases in patients undergoing dialysis. 41 The lack of all CgA peptides makes the CgA knockout mice (CgA-KO) more sensitive to insulin despite being obese. 42 In addition, opposite to wild-type (WT) mice, CgA-KO mice can maintain insulin sensitivity even after 4 months of high-fat diet (HFD).…”
Section: Introductionmentioning
confidence: 99%
“…Chromogranin A (CgA), a ~49 kDa proprotein, gives rise to peptides with opposing regulatory effects 32‐36 . Although pancreastatin (PST: hCgA 250‐301 ) is an anti‐insulin and proinflammatory peptide, 37,38 catestatin (CST: CgA 352‐372 ) is a proinsulin and anti‐inflammatory peptide 39,40 and is a risk factor for cardiovascular diseases in patients undergoing dialysis 41 . The lack of all CgA peptides makes the CgA knockout mice (CgA‐KO) more sensitive to insulin despite being obese 42 .…”
Section: Introductionmentioning
confidence: 99%